2014
DOI: 10.1158/1078-0432.ccr-14-1404
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Trial of Single-Agent Reolysin in Patients with Relapsed Multiple Myeloma

Abstract: Introduction Reolysin®, a proprietary isolate of reovirus Type 3 Dearing, enters and preferentially induces apoptosis of malignant cells. RAS pathway activation has been associated with more efficient reoviral infectivity and enhanced oncolysis. Reovirus is currently in advanced solid tumor phase 1 – 2 trials; no clinical trials have been conducted in patients with hematologic malignancies. Methodologies A phase 1 trial treated 12 relapsed myeloma patients at two dose levels. Reolysin was infused daily for 5… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 34 publications
2
65
0
Order By: Relevance
“…The following antibodies were used in this study: antibody to RVRV capsid protein (compliments of Dr. Matt Coffey of Oncolytics Biotech, Inc.), caspase-3 (1:33, antigen retrieval, cat#Ab4051, Abcam, Cambridge, MA), p38 (1:250, antigen retrieval, cat#Ab7952, Abcam, Cambridge, MA), p-p38 (pospho-T180/Y180; cat#Ab38238, Abcam, Cambridge, MA) and Junctional Adhesion Molecule 1 (JAM-1, 1:150 with antigen retrieval; cat#Ab52647, Abcam, Cambridge, MA), as previously described (14). Heat Mediated Antigen Retrieval was performed using Solution Antigen retrival pH 6.0 (cat#ab973, Abcam, Cambridge, MA ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following antibodies were used in this study: antibody to RVRV capsid protein (compliments of Dr. Matt Coffey of Oncolytics Biotech, Inc.), caspase-3 (1:33, antigen retrieval, cat#Ab4051, Abcam, Cambridge, MA), p38 (1:250, antigen retrieval, cat#Ab7952, Abcam, Cambridge, MA), p-p38 (pospho-T180/Y180; cat#Ab38238, Abcam, Cambridge, MA) and Junctional Adhesion Molecule 1 (JAM-1, 1:150 with antigen retrieval; cat#Ab52647, Abcam, Cambridge, MA), as previously described (14). Heat Mediated Antigen Retrieval was performed using Solution Antigen retrival pH 6.0 (cat#ab973, Abcam, Cambridge, MA ).…”
Section: Methodsmentioning
confidence: 99%
“…We recently reported that single agent Reolysin is safe and well tolerated in patients with relapsed MM (14). Our correlative analyses revealed that viral RNA, but not active viral replication, was evident in the patient’s MM cells approximately one week following initial RV treatment.…”
Section: Introductionmentioning
confidence: 99%
“…161,162 Moreover, the clinical profile of Imlygic Ò combined with the FDA-approved cytotoxic T lymphocyte-associated 4 (CTLA4)-targeting monoclonal antibody ipilimumab 163,164 has been assessed in 18 patients with unresectable Stage IIIB-IV melanoma (NCT01740297). 165 Reolysin Ò (a proprietary variant of reovirus serotype 3 -Dearing strain) 166 has been tested either as standalone immunotherapeutic agent in 12 myeloma patients and in 15 subjects with recurrent malignant gliomas, 167,168 or combined with low-dose cyclophosphamide 169,170 in 29 children with relapsed or refractory extra-cranial solid tumors (NCT01240538), 171 and in 36 individuals affected by advanced neoplasms. 172 The safety and efficacy of Cavatak TM (a proprietary variant of Coxsackievirus A21) 173 administered intratumorally or intravenously as standalone immunotherapeutic agent have been evaluated in 57 subjects with unresectable Stage IIIC-IV melanoma (NCT01227551), 174,175 and in 30 individuals with other advanced solid malignancies (NCT02043665).…”
Section: Completed Clinical Studiesmentioning
confidence: 99%
“…In this study reovirus strains T1L, T2J, and T3L were administered to 27 adult male prisoners (aged 21-38 years). Three groups of nine men each received intranasal inoculations of >10 6 TCID 50 (Tissue Culture Infective Dose 50 ) of a particular strain of reovirus. Within the group that received T1L, three individuals developed clinical illnesses with the symptoms of headache, pharyngitis, sneezing, rhinorrhea, cough, and malaise which began 24-48 h following the viral challenge and lasted for a maximum of 7 days.…”
Section: Reovirus and Human Diseasementioning
confidence: 99%
“…In the fi rst phase I combination study, reovirus was administered intravenously with gemcitabine in dose escalating cohorts to patients with advanced cancers [ 171 ]. With the observation of two dose 3 limiting toxicities, i.e., alanine aminotransferase and Troponin I increases the protocol was amended to a single dose of reovirus up to 3 × 10 10 TCID 50 . A potential interaction between reovirus and gemcitabine in causing liver enzyme increases noted in this study was associated with concomitant use of acetaminophen use.…”
Section: Reovirus In Combination With Radiation Therapymentioning
confidence: 99%